Prevalence and incidence of low back pain among runners: a systematic review - Maselli, F.; Storari, L.; Barbari, V.; Colombi, A.; Turolla, A.; Gianola, S.; Rossettini, G.; Testa, M. (BMC Musculoskeletal Disorders, 2020)
Background Running is one of the most popular sports worldwide. Despite low back pain (LBP) represents the most common musculoskeletal disorder in population and in sports, there is currently sparse evidence about prevalence, incidence and risk factors for LBP among runners. The aims of this systematic review were to investigate among runners: prevalence and incidence of LBP and specific risk factors for the onset of LBP. Methods A systematic review has been conducted according to the guidelines of the PRISMA statement. The research was conducted in the following databases from their inception to 31st of July 2019: PubMed; CINAHL; Google Scholar; Ovid; PsycINFO; PSYNDEX; Embase; SPORTDiscus; Scientific Electronic Library Online; Cochrane Library and Web of Science. The checklists of The Joanna Briggs Institute Critical Appraisal tools were used to investigate the risk of bias of the included studies. Results Nineteen studies were included and the interrater agreement for full-text selection was good (K=?0.78; 0.61-0.80 IC 95%). Overall, low values of prevalence (0.7-20.2%) and incidence (0.3-22%) of LBP among runners were reported. Most reported risk factors were: running for more than 6 years; body mass index >24; higher physical height; not performing traditional aerobics activity weekly; restricted range of motion of hip flexion; difference between leg-length; poor hamstrings and back flexibility. Conclusions: Prevalence and incidence of LBP among runners are low compared to the others running related injuries and to general, or specific population of athletes. View the low level of incidence and prevalence of LBP, running could be interpreted as a protective factor against the onset of LBP.